Monitoring of cytogenetic instability by micronuclei assay of both immunocompetent and non-immunocompetent cells in tick-borne encephalitis patients depending on variants of glutathione-S-transferase genes in the genotype - Nikolay Nikolaevich Ilyinskikh (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Aim of this study was to study the dynamics of the frequency of cytokinesis-blocked T-lymphocytes with micronuclei in peripheral blood and the frequency of buccal micronucleated epithelium cells for a period of half a year in patients with acute tick-borne encephalitis, depending on burden of active and inactive variants of glutathione-S-transferase genes (GSTM1 and GSTT1) in the patient's genotype. We carried out micronucleus assay in immunocompetent and non-immunocompetent cells in 54 patients with acute tick-borne encephalitis and 35 healthy persons (control) residing in the Tomsk and Tyumen regions. To analyze the frequency of cytokinesis-blocked micronucleated T-lymphocytes was used venous peripheral blood as material for phytohemagglutinin-stimulated cultures, and to study the frequency of buccal micronucleated cells, samples of the buccal mucous membrane epithelial cells were obtained. To carried out both techniques of micronucleus assay, cytological preparations were prepared, which were stained using the Giemsa or Felgen methods. The material for the study was obtained repeatedly during admission of patients to treatment, and also after 1 week, 1, 3 and 6 months.  Polymerase chain reaction was used to analyze the alleles of the GSTM1 and GSTT1 genes. As a result of this analysis was found a significant increase in the frequency of micronucleated cells in tick-borne encephalitis patients compared with the control group. In addition, the frequency of cytokinesis-blocked micronucleated T-lymphocytes was increased significantly higher than the one of micronucleated buccal cells. The most significant and prolonged increase in the frequency of micronucleated cells was associated with the mutant inactive variants of the genes GSTM1 (0/0) and GSTT1 (0/0). In the patients with burden the inactive forms of these genes, the cytogenetic instability of the cytokinesis-blocked blood T-lymphocytes could persist for up to six months. In case of buccal cells, the frequency of micronucleated cells was close to the one in the control group as early as 1-3 months after a course of treatment. Conclusion. It was found that the most increased and prolonged frequency of cytogenetically instable cells persisted in cytokinesis-blocked T-lymphocytes of peripheral blood of patients with tick-borne encephalitis who were carriers of the genotype with inactive variants of  both GSTM1 (0/0) and GSTT1 (0/0 ) glutathione-S-transferase genes.